Makna Pendidikan dalam Tradisi Pembacaan Al-Qur’an Tujuh Surat Pilihan di PP. Al-Munawwir Komplek Al-Fatimiyah Putri Krapyak Yogyakarta - Riastri, Remita; Musakal (Academy of Education Journal, 2024)
This study aims to explore the meaning of education in the tradition of reading seven selected surahs of the Al-Qur'an at the Al-Munawwir Islamic Boarding School, Al-Fatimiyah Putri Krapyak Complex, Yogyakarta, which serves as a medium for learning to read and memorize the Al-Qur'an. This tradition functions not only as a spiritual avenue but also as an effective teaching method for students to master reading and memorizing the Al-Qur'an correctly. The research employs a qualitative descriptive method with an ethnographic approach. Data collection was conducted using three techniques: observation, interviews, and documentation. Data analysis utilized a descriptive-explanatory approach, where the researcher provides an in-depth description of an object, phenomenon, or concept while explaining how it works and the reasons behind it. The findings indicate that this activity significantly enhances students' abilities to read and memorize the Al-Qur'an, particularly the seven selected surahs, while teaching the correct reading rules, including makharijul huruf and tajwid. Additionally, this tradition plays a role in shaping the character and discipline of the students, despite challenges in understanding the meaning and purpose of the activities. Based on the research findings, it can be concluded that the tradition of reading sthe seven selected surahs of the Al-Qur'an at the Al-Munawwir Islamic Boarding School, Al-Fatimiyah Krapyak Yogyakarta, is a highly effective educational medium, supporting the spiritual and academic development of the students and imparting beneficial moral values in their daily lives.